2016
DOI: 10.22323/2.15030207
|View full text |Cite
|
Sign up to set email alerts
|

Science learning via participation in online citizen science

Abstract: We investigate the development of scientific content knowledge of volunteers participating in online citizen science projects in the Zooniverse (http://www.zooniverse.org). We use econometric methods to test how measures of project participation relate to success in a science quiz, controlling for factors known to correlate with scientific knowledge. Citizen scientists believe they are learning about both the content and processes of science through their participation. We don't directly test the latter, but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 30 publications
1
72
0
4
Order By: Relevance
“…After reviewing 14 citizen science programs, Bela et al (2016) concluded that learning outcomes should be intentionally incorporated into citizen science. Masters et al (2016) showed that fully online citizen science programs ("citizen cyberscience") with strong communication and public engagement strategies (e.g., blogs and online chat forums) are more strongly characterized by active participation and learning outcomes than those without. Price and Lee (2013) advocate for finding new ways to support citizen scientists by creating online forums to support collaborative learning; they found that participants attributed much of their learning to interactions within the social forums connected to a citizen cyberscience project.…”
Section: Volunteer Motivationsmentioning
confidence: 99%
“…After reviewing 14 citizen science programs, Bela et al (2016) concluded that learning outcomes should be intentionally incorporated into citizen science. Masters et al (2016) showed that fully online citizen science programs ("citizen cyberscience") with strong communication and public engagement strategies (e.g., blogs and online chat forums) are more strongly characterized by active participation and learning outcomes than those without. Price and Lee (2013) advocate for finding new ways to support citizen scientists by creating online forums to support collaborative learning; they found that participants attributed much of their learning to interactions within the social forums connected to a citizen cyberscience project.…”
Section: Volunteer Motivationsmentioning
confidence: 99%
“…Many projects are explicitly designed to have citizen scientists experience the scientific processes; thus, Bonney et al [2009] concluded that most citizen-science projects are designed to help citizen scientists learn scientific knowledge to some degree. Consistent with these efforts, volunteers of citizen-science projects reported that they actually learned about science by participating in the projects [e.g., Brossard, Lewenstein and Bonney, 2005;Land-Zandstra et al, 2016a;Masters et al, 2016].…”
Section: Learning About Sciencementioning
confidence: 99%
“…This predominance of male participants has been observed in other online citizen science projects, not just in DC (Curtis 2015a;2015b;Masters et al 2016;Raddick et al 2013;Reed et al 2013). Surveys into public attitudes towards science and technology may explain this finding to some extent.…”
Section: Discussionmentioning
confidence: 59%
“…Within the broader context of online citizen science, this work also demonstrates that Folding@home has some features in common with other projects such as demographic characteristics, motivations for participation, and variable levels of contribution (Curtis 2015a(Curtis , 2015bMasters et al 2016;Ponciano et al 2014;Raddick et al 2013;Reed et al 2013).…”
Section: Discussionmentioning
confidence: 73%